The Oxford junior dictionary - Sansome, Rosemary; Reid, Dee Spooner, Alan (Oxford University Press Oxford, 2003)
This dictionary is specially written to support young users in their reading and writing both at school and at home. Trialled and tested in schools, it contains 13,000 words and phrases.